State Bar's Public Protection Committee Hearing on Unlicensed Practice of Law - Watkins, Howard::::::::: (1987)
Fresno County Bar Association President Howard Watkins welcoming the State Bar Panel to Fresno Panel Vice-Chair and with the Fresno County's Consumer Protection Office is 2nd from right